Modulation of the EGFR Signalling Pathway Through Protein Tyrosine Phosphatase PTPN12 Stimulates Asymmetric Division of Dystrophin Deficient Satellite Stem Cells - Lofaro, Stephanie (Université d'Ottawa / University of Ottawa, 2025)
Duchenne muscular dystrophy (DMD) is a severe muscle wasting disease that manifests during early childhood, rapidly progressing from motor delays to respiratory and cardiac failure, leading to premature death. The disease gene, DMD, encodes for the dystrophin protein that is essential in the stabilization of myofibers. In DMD the absence of dystrophin results in fragile myofibers that are highly susceptible to injury, undergoing constant degeneration. Contributing to muscle weakness, the regeneration of these myofibers is impaired due to an intrinsic defect in dystrophin-deficient satellite cells. This defect results in the impairment of satellite cell polarity establishment and asymmetric division, leading to increased satellite cell self-renewal and fewer committed myogenic progenitors that facilitate muscle repair. Activation of the EGFR-AURKA pathway in satellite cells has been shown to induce apicobasal asymmetric divisions, enhancing myofiber repair and formation in dystrophin deficient muscle. With this information, we chose to explore the protein target PTPN12 aimed to modulate the EGFR-AURKA signalling pathway. However, the role of PTPN12 in satellite cells remains unclear. Here we uncover that PTPN12 is highly expressed in satellite cells and that negative modulation of PTPN12 in dystrophin-deficient myogenic cells augments EGFR activation, driving apicobasal polarity and in turn promoting asymmetric divisions. This shift toward asymmetric division following modulation of PTPN12 enhances satellite cell response following muscle injury, improving dystrophic muscle morphology. Modulation of PTPN12 through the small molecule inhibitor SAT-732 further confirms these findings, leading to improvements in force generation of dystrophic muscle. This research provides a novel advancement in our current disease understanding, setting the stage for the potential clinical application of EGFR modulators to restore polarity dysregulation and muscle regeneration in DMD, thereby improving patient quality of life and overall lifespan.
Keywords: Satellite Cells; Duchenne Muscular Dystrophy; Muscle Regeneration; PTPN12; Asymmetric Division; Myogenesis; Cell Division; Epidermal Growth Factor Receptor; Aurora Kinase A; Cell Polarity